How a routine checking of Escherichia coli in retailed food of animal origin can protect consumers against exposition to Campylobacter spp. and Listeria monocytogenes? - Trajković-Pavlović Ljiljana; Novaković Budimka; Martinov-Cvejin Mirjana; Gusman Vera; Bijelović Sanja; Dragnić Nataša; Balać Dragana (Vojnosanitetski Pregled)
Background/Aim. According to the literature that has been published over the last two decades Campylobacter spp i Listeria monocitogens can be identified as causes of numerous diseases derived by consuming food of animal origin. The purpose of this paper was to find out how established national microbiological criteria of the Republic of Serbia on food safety in retailed food of animal origin could contribute to consumer's protection against exposition to foodborne pathogens such as Campylobacter spp. and Listeria monocytogenes. Methods. During a routine microbiological safety control of randomly selected 60 samples of fresh poultry meat, 30 samples of other fresh meat readymade for grilling, 30 samples of sausage products, 37 samples of heattreated meat, 39 samples of toppings for fast food of animal origin and 31 samples of dairy products a national food safety criteria (Escherichia coli, aerobic plate count, Salmonella spp., coagulasa positive Staphylococcus, Proteus spp., sulphitoreducting Clostridia) were applied and, as well as, testing to Campylobacter spp. and Listeria monocitogens. In determination of Campylobacter spp. and Listeria monocytogenes, food quality control methods of the Food and Agriculture Organization (FAO) were applied, while in determination of the other above motioned bacteria, national provisions on microbiological methods were applied who are adjusted to the FAO ones. Results. Related to the national criteria on microbiological food safety, 88 (38.8%) samples, out of the total 227 tested, were rejected. When to these results, the results of laboratory tests on Listeria monocytogens were added, a terminal number of rejected samples were not changed. When to these results, the results of Campylobacter spp. testing were added, 91 (40.1%) out of the 227 samples were unsatisfied. Results of logistic regression model with occurrence of Escherichia coli as dependent variable indicated that Escherichia coli was 4.5 times likely to occur among samples with Campylobacter spp. than among samples without Campylobacter spp. (OR = 4.515, 95% CI: 1.019-20.002). Sensitivity of the fitted model (Hosmer-Lemeshow p = 0.268) was 76.8% and its specificity was 75.0%. At the same time Escherichia coli was confound in all (100%) food samples that were contaminated by Listeria monocytogenes. Conclusion. Statistical analysis indicated that Escherichia coli was completely sensitive to identify all samples contaminated with Listeria monocytogenas and highly sensitive to identify samples contaminated with Campylobacter spp. Nevertheless, 3 (1.3%) of the tested samples were not covered with Escherichia coli.